Comprehensive sexual health assessments for adolescents. Issue 8 (16th December 2020) - Johnson, Natasha
Abstract: Sexual activity and experimentation are normative parts of adolescent development that may, at the same time, be associated with adverse health outcomes, including the acquisition of sexually transmitted infections, unplanned pregnancy, and teen dating violence. Anticipatory guidance regarding sexual and reproductive health for teens should address normal sexual development issues, such as identity and attractions, safe relationships, safer sex, and contraception. Health care providers can enhance the sexual education of the youth they see and help mitigate negative health outcomes. This practice point offers a '7-P' approach to ensure that health care providers obtain comprehensive sexual health assessments for adolescents. Teen issues such as identity, confidentiality, and consent, and dating violence are discussed, and Canadian Paediatric Society resources are cited to provide more detailed care pathways on related issues: contraception, pregnancy, and sexually transmitted infections.